ATG8 delipidation is not universally critical for autophagy in plants - Zou, Yong; Ohlsson, Jonas A.; Holla, Sanjana; Sabljić, Igor; Leong, Jia Xuan; Ballhaus, Florentine; Krebs, Melanie; Schumacher, Karin; Moschou, Panagiotis N.; Stael, Simon; Üstün, Şuayıb; Dagdas, Yasin; et al. (Nature Communications, 2025)
Intracellular recycling via autophagy is governed by post-translational modifications of the autophagy-related (ATG) proteins. One notable example is ATG4-dependent delipidation of ATG8, a process that plays critical but distinct roles in autophagosome formation in yeast and mammals. Here, we aim to elucidate the specific contribution of this process to autophagosome formation in species representative of evolutionarily distant green plant lineages: unicellular green alga Chlamydomonas reinhardtii, with a relatively simple set of ATG genes, and a vascular plant Arabidopsis thaliana, harboring expanded ATG gene families. Remarkably, the more complex autophagy machinery of Arabidopsis renders ATG8 delipidation entirely dispensable for the maturation of autophagosomes, autophagic flux, and related stress tolerance; whereas autophagy in Chlamydomonas strictly depends on the ATG4-mediated delipidation of ATG8. Importantly, we also demonstrate the distinct impact of different Arabidopsis ATG8 orthologs on autophagosome formation, especially prevalent under nitrogen depletion, providing new insight into potential drivers behind the expansion of the ATG8 family in higher plants. Our findings underscore the evolutionary diversification of the molecular mechanism governing the maturation of autophagosomes in eukaryotic lineages and highlight how this conserved pathway is tailored to diverse organisms.